A Proposed Vision for the Empowerment of Saudi Woman in the Transport Sector A Comparative Study - Al-Turif, Ghada H. (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed at developing a proposed vision to empower woman in the transport and transportation sector by knowing the impact of the decision to allow woman to drive cars on her social and economic empowerment and the obstacles they face. There were 320 individuals in different regions of the Kingdom of the Saudi Arabia (KSA) including (135 males, 185 females), where the data were collected by a questionnaire. In addition to a sample of (20) experts and specialists in the transport sector, and specialists in sociology and social service to develop a proposed vision for woman’s empowerment in the transport and transportation sector. The study was conducted during 2019. .